ISSP 2004 - Citizenship I: Sweden - Edlund, Jonas; Svallfors, Stefan (Umeå University, 2009)
This survey is the Swedish part of the 2004 'International Social Survey Program' (ISSP), and it is the first ISSP-survey focusing on citizenship.

There are different opinions as to what it takes to be a good citizen and the respondents were asked to indicate on a scale 1 to 7 how important different behaviours are to make a good citizen. Respondents were also asked if different groups in society, such as religious extremists, people who want to overthrow the government by force, or people prejudiced against any racial or ethnic group, should be allowed to hold public meetings. Other questions dealt with different forms of political action that people can take. Respondents had to indicate whether they had signed a petition; boycotted or deliberately bought certain products; demonstrated; attended a political meeting; contacted a politician or civil servant to express a certain view; or joined an Internet political forum, in the past year or in a more distant past. If the respondent never had done an activity, they were asked if they might do it or would never under any circumstances do it. Respondents also had to indicate if they belonged and actively participated in different kinds of groups and associations. On a scale 1 to 7 respondents had to give their opinion on people´s rights in a democracy. Demographic variables include age, sex, education, marital status, personal and family income, employment status, household size and composition, occupation, religion, social class, union membership, political orientation, and demographics of community.

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 2004 investigating Social Citizenship.

Detta är den svenska studien inom det internationella forskningsprojektet ISSP. Temat för studien 2004 är ”Social Citizenship". Detta är första gången studien genomförs på det här temat.

International Social Survey Program, ISSP, är ett globalt forskningsprojekt som har till uppgift att konstruera och genomföra internationellt jämförbara attitydstudier. Sedan 1985 har attityddata årligen samlats in och utgör nu en databas som är fritt tillgänglig för forskarsamhället. I dagsläget är 48 länder, från sex olika världsdelar, involverade i projektet. Genom bredden av medlemsländer skapas möjlighet till jämförelser i flera dimensioner. Det finns möjligheter att både jämföra länder som har en likartad samhällsstruktur och historia, och länder som skiljer sig påtagligt från varandra.

Sverige har varit medlem i ISSP sedan 1992 och det är Sociologiska intuitionen vid Umeå universitet som är huvudman för studierna i Sverige.

Sedan starten 1985 har attityder från flera olika områden undersökts. Vissa områden har återkommit genom åren, vilket gör det möjligt att även jämföra dem över tid. Följande ämnen har behandlats:

1985 The Role of Government I
1986 Social Networks I
1987 Social Inequality I
1988 Family and Changing Gender Roles I
1989 Work Orientations I
1990 The Role of Government II
1991 Religion I
1992 Social Inequality II
1993 Environment I
1994 Family and Changing Gender Roles II
1995 National Identity I
1996 The Role of Government III
1997 Work Orientations II
1998 Religion II
1999 Social Inequality III
2000 Environment II
2001 Social Networks II
2002 Family and Changing Gender Roles III
2003 National Identity II
2004 Social Citizenship I
2005 Work Orientations III
2006 Role of Government IV
2007 Leisure and Sports I
2008 Religion III
2009 Social Inequality IV
2010 Environment III
2011 Health
2012 Family, Work and Gender Roles IV
2012 Family, Work and Gender Roles IV

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. Studien för 2004 undersöker åsikter om medborgarskap.
ISSP 2004 - Åsikter om medborgarskap
Keywords: citizenship; medborgarskap; citizenship skills; medborgerliga färdigheter; political extremism; politisk extremism; political action; politisk handling; civil and political rights; medborgerliga och politiska rättigheter; freedom of expression; uttrycksfrihet; protest movements; proteströrelser; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology; Sociologi